2012
DOI: 10.1172/jci61931
|View full text |Cite
|
Sign up to set email alerts
|

Suppressing T cell motility induced by anti–CTLA-4 monotherapy improves antitumor effects

Abstract: A promising strategy for cancer immunotherapy is to disrupt key pathways regulating immune tolerance, such as cytotoxic T lymphocyte-associated protein 4 (CTLA-4). However, the determinants of response to anti-CTLA-4 mAb treatment remain incompletely understood. In murine models, anti-CTLA-4 mAbs alone fail to induce effective immune responses to poorly immunogenic tumors but are successful when combined with additional interventions, including local ionizing radiation (IR) therapy. We employed an established … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
149
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 176 publications
(165 citation statements)
references
References 85 publications
16
149
0
Order By: Relevance
“…injection of a-CTLA-4 antibodies during the course of imaging). The results from both lines of experiments showed that a-CTLA-4 antibodies seem to increase T-cell motility and are consistent with the results of several published reports (16,17,23).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…injection of a-CTLA-4 antibodies during the course of imaging). The results from both lines of experiments showed that a-CTLA-4 antibodies seem to increase T-cell motility and are consistent with the results of several published reports (16,17,23).…”
Section: Discussionsupporting
confidence: 91%
“…2B-E). These results are consistent with published data on the effects of a-CTLA-4 antibodies on T-cell mobility (16,17).…”
Section: Pmel-1 Dynamics In Tumors Are Affected By Chronic Ctla-4 Blosupporting
confidence: 93%
See 3 more Smart Citations